Soluble LH-HCG receptor and oestradiol as predictors of pregnancy and live birth in IVF. Issue 2 (February 2019) - Chambers, Anne Elizabeth; Fairbairn, Craig; Gaudoin, Marco; Mills, Walter; Woo, Irene; Pandian, Raj; Stanczyk, Frank Z.; Chung, Karine; Banerjee, Subhasis
Abstract: Research question: Circulating soluble LH-HCG receptor (sLHCGR) is a first-trimester marker for screening pregnancy pathologies and predicts premature or multiple births before fertility treatment. Oestradiol per oocyte at ovulation induction predicts IVF treatment outcomes. We asked whether sLHCGR levels are stable during fertility treatment and whether, alone or with oestradiol, they could improve prediction of fertility treatment outcomes. Design: Serum sLHCGR, anti-Müllerian hormone [AMH] and oestradiol were measured in patients undergoing IVF. Antral follicle count before ovarian stimulation and oocyte yield were used to establish sLHCGR– oocyte ratio (SOR), sLHCGR– antral follicle ratio (SAR), oestradiol at trigger per oocyte (oestradiol–oocyte ratio [EOR]) and oestradiol at trigger per antral follicle (oestradiol–antral follicle ratio [EAR]). Results: The relatively stable sLHCGR was negatively related to AMH when oocyte yield was high. The sLHCGR levels were proportional (r = 0.49) to oestradiol at early cycle (day-3). Pregnancy and live birth were highest at low sLHCGR (≤1.0 pmol/ml) and SOR (≤ 0.1 pmol/ml/oocyte). A total of 86–89% of live births in IVF treatment were within the cut-off parameters of SAR and SOR (0.5 pmol/ml) and EAR and EOR (380 pg/ml). For failed pregnancy, age, SOR and EOR together had positive and negative predictive values of 0.841 and 0.703, respectively. Conclusions: sLHCGR levels are negatively related to AMH when oocyte yield is high. High early cycle sLHCGR is associated with elevated day-3 oestradiol. Low sLHCGR and SOR are indicators of increased clinical pregnancy and live birth rates. Patient age and SOR, combined with EOR, might improve prediction of IVF treatment outcomes.